Accumulation of setting particles in some coral reef areas of Peninsular Malaysia - Lee, Jen Nie; Che Abd Rahim Mohamed, (Universiti Kebangsaan Malaysia, 2011)
The aim of this study was to determine the accumulation of settling particles in coral reefs of Peninsular Malaysia. Settling particles were collected from the coral reefs of Port Dickson, Pulau Langkawi, Pulau Tioman, Pulau Redang and Pulau Tinggi from 2005 to 2008. The average total settling particles in Pulau Langkawi and Port Dickson was 49.8 mg/cm2/day, while for Pulau Tioman, Pulau Redang, and Pulau Tinggi was 3.5 mg/cm2/day. The results showed that accumulations rate in west coast were higher than east coast of Peninsular Malaysia. However, Pulau Tioman in the east coast received high accumulations rate of settling particles in certain times of the year due to sediment resuspension at shallow reefs caused by high energy seasonal yearly wave and monsoon